2007
DOI: 10.1002/jmv.20831
|View full text |Cite
|
Sign up to set email alerts
|

Human parechovirus 1 infections in young children—no association with type 1 diabetes

Abstract: The epidemiology, transmission and clinical symptoms of human parechoviruses [HPeV, classified earlier as enteroviruses; echovirus 22 (HPeV1) and echovirus 23 (HPeV2)] remain poorly characterized. Enteroviruses and one parechovirus species, the Ljungan virus, have been associated with type 1 diabetes in humans and rodents. The occurrence of human parechovirus 1 (HPeV1) infections in young children and their possible association with type 1 diabetes was evaluated. The prospective birth cohort study comprised 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
1
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 36 publications
13
56
1
3
Order By: Relevance
“…Ljungan virus has earlier been shown to cause diabetes-like condition in rodents (Niklasson et al, 2006), but was not identified in samples from children in our studies (Tapia et al, 2008, Tapia et al, 2010. HPeV1 has been reported to show no association with T1D (Tauriainen et al, 2007), but there is no data on the other types of HPeVs. However, sequencing should be done to see if there is any difference in strains, and to test for all the new human Parechoviruses.…”
Section: Picornaviruscontrasting
confidence: 65%
“…Ljungan virus has earlier been shown to cause diabetes-like condition in rodents (Niklasson et al, 2006), but was not identified in samples from children in our studies (Tapia et al, 2008, Tapia et al, 2010. HPeV1 has been reported to show no association with T1D (Tauriainen et al, 2007), but there is no data on the other types of HPeVs. However, sequencing should be done to see if there is any difference in strains, and to test for all the new human Parechoviruses.…”
Section: Picornaviruscontrasting
confidence: 65%
“…Data on seroprevalence in neonates are not available, but the seroprevalence rate for children between 7-12 months is 15% which steadily increases to 91% in adolescent adults only to decline again to 56-87% in adults. This is in contrast to what is seen for HPeV1 where over 97% of adults still have antibodies against HPeV1 (Joki- Korpela & Hyypia, 1998;Tauriainen et al, 2007). Interestingly, seroprevalence among adults in the childbearing age (20-39 years) is the lowest (57-74%) (Ito et al, 2004).…”
Section: Risk Groups For Hpev Infectionsmentioning
confidence: 77%
“…The seroprevalence decreased after 6 months of age, only to rapidly increase among children older than 1-3 year of age to 95%. The low seropositivity from 6 months to 1-3 years is marked by an increase in infection frequencies among children in this age group, (Benschop et al, 2006a;Joki-Korpela & Hyypia, 1998;Stanway et al, 2000;Takao et al, 2001;Tauriainen et al, 2007). Seroprevalence rates among adults remained stable at 97-99% (Joki-Korpela & Hyypia, 1998;Stanway et al, 2000;Tauriainen et al, 2007).…”
Section: Risk Groups For Hpev Infectionsmentioning
confidence: 99%
See 2 more Smart Citations